1988
DOI: 10.1111/j.2042-7158.1988.tb06286.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute and Chronic Administration of Morphine and Morphine Withdrawal on Intestinal Transit Time in the Rat

Abstract: The effects of acute and chronic morphine administration and of morphine-withdrawal on intestinal transit time of a liquid meal were investigated using rats. Many experiments have assessed the effects of acute morphine administration on intestinal transit, but the intestinal effects of chronic morphine administration have been neglected. Our results showed no significant differences between morphine-dependent and control animals when assessing the leading edge of the liquid meal infusion, its distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…There is some evidence that morphine stimulates mucosal sensory receptors, which, in turn, activate a reflex arc to increase fluid absorption further [24]. The mechanism of the antisecretory effect of opioids has been shown to be indirect.…”
Section: Opioid Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…There is some evidence that morphine stimulates mucosal sensory receptors, which, in turn, activate a reflex arc to increase fluid absorption further [24]. The mechanism of the antisecretory effect of opioids has been shown to be indirect.…”
Section: Opioid Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…The diarrhoea that is produced on opiate withBrkish Joumal of Phannacology (1995) U4. 152-156 drawal in this species is associated with a decrease in intestinal fluid absortion (Chang et al, 1984) and increased intestinal motility (Brown et al, 1988 (Coupar & Hancock, 1994). The specific aim of this study was to characterize the receptor mediating one of these effects, namely inhibition of intestinal fluid secretion, using a range of metabolically stable adenosine analogues with different potencies and degrees of specifity for adenosine receptor subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Naloxone was given to the animals subcuta neously in a volume of 0.25 ml of saline 30 min prior to commencing the experiment. The dose of naloxone chosen for this study w'as within the range used for this class of receptors and has previously been shown to antagonise either the effect of an opiate agonist or gas trointestinal motility [6,7], Experimental Protocol Breath Hydrogen Technique. A total of 8 animals were used for this part of the study.…”
Section: Preparation O F Test Substancesmentioning
confidence: 99%